Untold Stories of Displaced Rohingya Pregnant Women Exposed to Intimate Partner Violence in Camp Settings - Dowllah, Istiaque Mahmud (2024)
Intimate partner violence (IPV) strongly impacts the physical, sexual, social, and reproductive health of women, causing an array of psychological and behavioural problems. During pregnancy, the detrimental effects of violence extend to both the mother and the child. Rates of IPV are frequently higher among those in conflict‐affected and displaced communities, most of whom live in low and middle‐income countries. IPV against Rohingya women is common due to relocation, family breakups, patriarchal norms, and deep‐seated gender roles. Despite the high prevalence of IPV in Rohingya refugees in Bangladesh, the matter is often under‐examined. This qualitative study aims to explore and understand pregnant IPV victims’ unique experiences and hardships among the displaced population in a camp setting. A sample of six pregnant homemakers with no formal education was recruited from a healthcare service provider in Leda Camp 24, a remote camp in Cox’s Bazar, Bangladesh. Semi‐structured, in‐depth, face‐to‐face interviews were conducted. Participants reported diverse manifestations of IPV victimisation. Physical abuse, emotional abuse, economic abuse, sexual abuse, pregnancy‐related consequences, and impact on mental health were commonly experienced by participants of this study. The current research investigates the recurrent abuse experienced by this demography, providing detailed narrative information beyond quantitative descriptions of IPV experiences. This article contributes to the existing knowledge on the intersection of IPV, pregnancy, and mental health among displaced populations. Governmental and non‐governmental stakeholders must contextualise these findings in policies and practices by integrating IPV and violence screening, prevention, and treatment protocols into refugee camps and healthcare service providers.